Multistate Hidden Markov Model for Health Insurance Premium Calculation - Utami, Rianti Siswi (2014)
Health conditions over time can be modelled using multistate Markov model. However, the information about health conditions is not always available, but there is another information related to this condition. This paper presents hidden Markov model to estimate transition intensity and observation probability for multistate model where the true state is not observed. The estimation of transition intensity and transition probability will be used to calculate health insurance premium. By using this method, it is expected to get an appropriate premium value. This method will be applied to patient’s visit in a clinic in West Java.